Does Culture Strengthen or Break Organization? Revisiting Organizational Culture’s Roles in Organizational Social Life - Suryani, Adi; Soedarso, Soedarso; Muhibbin, Zainul; Rahmawati, Deti; Hamdan, Fairuz Zahirah Zihni (BASKARA : Journal of Business and Entrepreneurship, 2024)
As a collection of individuals who work together to achieve organizational goals, the organization urgently needs glue which attaches all members. Existing studies find that organizational culture can be a means to provoke collectivism climate for influencing organizational performance. The study aims to examine the potential capacity of organizational rituals of arisan and picnic in evoking organizational social cohesion, from the perspective of organizational members. Furthermore, it aims to explore the other possible functions of organizational culture. The data are collected from co-reflection by using certain reflection guidance. The study finds that organizational arisan or picnic can potentially benefit members. It provides opportunities for members to share happy moments, face challenging activities together, forget their conflict and replace it with new happy experiences. However, this ritual does not always bring genuine happiness. It may keep silent storm of emotion as the ritual can exert social pressure, display dominant social status, reinforce power of giving which acquire needs to get back (return the kindness). The study also reveals the emergent co-rituals which are created or joined by in-group members. Co-exist rituals allow members to fit their individual-group dimensions with less social pressure, build stronger emotional bond and support. However, this too strong emotional tie may ignite inter-group conflict and high competition with other groups.